Subchronic toxicity of oral deltamethrin in laying chickens - Liu, Yiming; Han, Mingyue; Liu, Chunshuang; Tang, Yaoxin; Jia, Ming; Chen, Xiaojie; Liang, Haijun; Gao, Yunfeng; Gu, Xu (Frontiers in Veterinary Science, 2022)
Pyrethroid pesticides, with low toxicity to birds and mammals and short persistence in the environment, are widely used now. With the development of intensive poultry farming, pesticide application leads to residues in poultry products and pollution in ecological environment. The aim of the present study was to examine deltamethrin subchronic toxicity in laying chickens. One hundred and twelve laying chickens were randomly assigned to 14 groups including 13 groups medicated with deltamethrin (n = 8) and one unmedicated group used as control (n = 8). Tissue samples were collected during and after administration for weighing and histopathological analysis. A single dose of deltamethrin (20 mg·kg−1·BW·d) was administered orally to laying chickens for 14 days. The results showed that deltamethrin has no significant effect on the relative organ weight of laying chickens (p > 0.05). The activities of aspartate aminotransferase and cholinesterase in the plasma gradually decreased over time in the medicated group (p < 0.05). Plasma concentrations of urea nitrogen, uric acid, cholesterol, triglycerides, and creatinine significantly increased during treatment (p < 0.05), and significant liver damage and loss of intestinal villous epithelium were observed. The intestinal wall thickness, villus height, and crypt depth of laying chickens were altered by deltamethrin treatment. During treatment was withdrawn, the intestinal repair was more extensive than the liver repair.